Digitalisasi Desa Wisata untuk Optimalisasi Promosi Pariwisata dan Budaya di Desa Batuan Kabupaten Gianyar - Widyanaputri, Ida Ayu Mega; Utami, Nengah Widya; Dewi, Putri Anugrah Cahya (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Tourism is one of the main sectors in economic growth in several countries in the world. A well-developed tourism sector can make a great contribution to a region. In Indonesia, tourism is one of the most important sources of income, especially in Bali, which is one of the most popular tourist destinations in the world. One of the interesting destinations in Bali is the Batuan Tourism Village. Batuan Tourism Village has indeed planned from the beginning to create a website that is specifically for Tourism Villages only, because it has the goal of focusing more on the Tourism Village website only so that tourists can more easily find tourist destinations they want to visit. Batuan Village apparently still has difficulties in introducing its cultural and artistic tourism to prospective tourists who want to come. With the problems that have been explained, the researcher provides a solution in the form of a website that focuses on the tourism sector in the Batuan Tourism Village. The results of the post-test evaluation given to the village staff showed good results after the website management training was held.